12-10x+15x=-18

Simple and best practice solution for 12-10x+15x=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-10x+15x=-18 equation:


Simplifying
12 + -10x + 15x = -18

Combine like terms: -10x + 15x = 5x
12 + 5x = -18

Solving
12 + 5x = -18

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 5x = -18 + -12

Combine like terms: 12 + -12 = 0
0 + 5x = -18 + -12
5x = -18 + -12

Combine like terms: -18 + -12 = -30
5x = -30

Divide each side by '5'.
x = -6

Simplifying
x = -6

See similar equations:

| P+10=11P^2-P+1 | | X-43=56 | | z^2-2*z+i=0forz | | z^2-2*z+i=0 | | pi*0.65= | | (x+5)*(x-2-3i)*(x-2+3i)=0 | | k^2+5k-4=0 | | 3x^2-13x-70=0 | | z^2-(3-2*i)z+1-3*i=0 | | 13-6x=9-7x | | 1/x*2x^2 | | x-4(x-2)=2(x-3) | | 6v-4y=x | | 7+49x=12x+19 | | 7-3(x-2)=-7(2-x) | | 2sin^2(x)+2=7cosx | | 2x^2+24x-40=0 | | 5x-2(3-x)=-4(x+5) | | x*10-3=3 | | z*10-9=8 | | 2(11x+5)=-3(4-3x)+5 | | 6xy+2z+4p-2p=o | | (3x^4-2y)(x^2+4y)=100 | | 23x+56x=345 | | 7(4y-5)=3(t+3) | | 8(4x+1)=5(2z+1) | | 4(r-2)=36 | | 3(q+7)=45 | | 3-4(x+2)=-5+4(x-5) | | 5p-7=18 | | 3x/1/10 | | 2x-7=7x+4 |

Equations solver categories